A layered mordenite and its synthesis method and application

By using pentylene amine or hexanediamine as additives, layered mordenite is synthesized in a one-step hydrothermal method, which solves the complex and cost problems of synthesis methods in the prior art, and achieves efficient and simple mordenite synthesis, improving catalytic performance and product stability.

CN119774634APending Publication Date: 2025-04-08CHINA CATALYST HLDG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411983831.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing mordenite synthesis methods have problems such as expensive, troublesome steps and affecting the hydrothermal stability of the catalyst, making it difficult to achieve easy-to-get raw materials, low-cost and easy-to-operate synthesis.

Method used

Pentyrene or hexanediamine is used as a new additive to directly synthesize layered mordenite by one-step hydrothermal method, avoiding the use of additional seeds and simplifying the synthesis process.

Benefits of technology

The efficient synthesis of mordenite is achieved, which reduces production costs, simplifies steps, improves product consistency and repeatability, and promotes the surfactivity and catalytic properties of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774634A_ABST
    Figure CN119774634A_ABST
Patent Text Reader

Abstract

The present invention provides a layered mordenite and a synthesis method and application thereof, and relates to the technical field of mordenite synthesis. The layered mordenite of the present invention is prepared by mixing, stirring, crystallizing, drying and calcining raw materials, wherein the raw materials include a silicon source, an aluminum source, an alkali source, an auxiliary agent and water; the silicon source is C-type silica gel, and the auxiliary agent is pentamethylenediamine or hexamethylenediamine. The synthesis method of the layered mordenite provided by the present invention is simple, economical and easy to industrialize, and can be used to prepare a Ti-MOR catalyst with excellent performance, and has significant technical advantages and broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mordenite synthesis, in particular to a layered mordenite and a synthesis method and application thereof. Background Art

[0002] Mordenite (MOR) is a silica-alumina zeolite molecular sieve with multi-layer overlapping crystal structure. Along the c-axis direction, there are two parallel main pores, namely, twelve-membered rings and eight-membered rings surrounded by four-membered rings and five-membered rings. Among them, different twelve-membered ring pores are connected by eight-membered ring side pockets along the b-axis direction. The twelve-membered rings (0.67×0.70nm) of MOR are large in size and easy to accumulate carbon deposits, resulting in pore blockage; while the eight-membered rings (0.28×0.57nm) are small in size and cannot achieve the diffusion of reactant molecules. Therefore, the eight-membered rings of MOR become the catalytic active center of carbonylation reaction. MOR has suitable acidity, unique pore structure, large specific surface area and pore volume, excellent catalytic stability and thermal stability. It is widely used in dimethyl ether carbonylation, normal alkane isomerization, toluene disproportionation, xylene isomerization, volatile organic matter and gas adsorption separation in industry.

[0003] For the above reasons, the synthesis of MOR has always been an important research topic in industrial chemistry. At present, some reliable methods for synthesizing MOR have been developed, including the use of quaternary ammonium salt structure directing agents, the addition of alkali metal fluorides, and the addition of MOR seeds. However, the above methods are expensive, cumbersome, and affect the hydrothermal stability of the catalyst. Therefore, the development of a new method for synthesizing MOR with readily available raw materials, low cost, and simple operation has important theoretical significance and application value. Summary of the invention

[0004] In view of this, the present invention provides a layered mordenite and a synthesis method and application thereof. The method provided by the present invention can directly synthesize mordenite by a one-step hydrothermal method using pentamethylenediamine or hexamethylenediamine as a new auxiliary agent without adding seed crystals. The mordenite synthesized by the present invention has a layered crystal morphology, the synthetic raw materials are easily available, the synthetic steps are simple, and it is conducive to further industrial production. The mordenite synthesized by the present invention can be used to prepare Ti-MOR catalysts.

[0005] The layered mordenite provided by the present invention is prepared by mixing, stirring, crystallizing, drying and calcining raw materials, wherein the raw materials include a silicon source, an aluminum source, an alkali source, an additive and water;

[0006] The silicon source is C-type silica gel; the aluminum source is aluminum hydroxide; the alkali source is sodium hydroxide; and the auxiliary agent is pentamethylenediamine or hexamethylenediamine.

[0007] Preferably, the aluminum source is calculated as aluminum oxide, the silicon source is calculated as silicon oxide, and the alkali source is calculated as sodium oxide. The molar ratio of aluminum oxide, silicon oxide, sodium oxide, additive and water in the raw materials is 1:(8-31.5):(2.25-4.75):(0.6-5):(300-450).

[0008] The present invention also provides a method for preparing the layered mordenite, comprising the following steps:

[0009] After deionized water, alkali source and aluminum source are evenly mixed, auxiliary agent and silicon source are added in sequence, and the mixture to be crystallized is obtained after stirring. The mixture to be crystallized is then crystallized. After the crystallization is completed, the solid product is washed with water to neutrality, dried and calcined to obtain mordenite.

[0010] Preferably, the crystallization temperature is 160° C. to 170° C., and the insulation time is 22 to 34 hours.

[0011] Preferably, the drying temperature is 80° C. to 120° C., and the drying time is 12 to 14 hours.

[0012] Preferably, the calcination temperature is 500° C. to 600° C., and the calcination time is 4 to 6 hours.

[0013] The present invention provides an application of mordenite in preparing a Ti-MOR catalyst. The mordenite is the mordenite described in the above technical solution.

[0014] Compared with the prior art, the beneficial technical effects of the present invention are:

[0015] Compared with the prior art, the layered mordenite and its synthesis method and application of the present invention have the following beneficial technical effects:

[0016] The present invention uses pentamethylenediamine or hexamethylenediamine as a novel auxiliary agent, and can realize the preparation of mordenite without adding external crystal seeds in the hydrothermal synthesis process, which not only simplifies the synthesis process, but also reduces the production cost, avoids the unstable factors caused by external crystal seeds, and improves the consistency and repeatability of the product.

[0017] The present invention uses pentamethylenediamine or hexamethylenediamine as an auxiliary agent, which can effectively control the crystal morphology of mordenite and promote the formation of its layered structure, making the synthesis process more efficient and easy to industrialize.

[0018] The synthesis method provided by the present invention has simple steps and is easy to operate. The layered mordenite can be obtained through simple mixing, stirring, crystallization, drying and calcining steps, which greatly simplifies the traditional synthesis process and improves production efficiency.

[0019] The mordenite crystal morphology synthesized by the present invention is layered, and this structure helps to improve the surface activity and catalytic performance of the catalyst, while ensuring the stability of the material in the catalytic reaction.

[0020] The raw materials used in the present invention are easily available and cheap, the temperature and time conditions required in the preparation process can be precisely controlled, thereby ensuring the quality of the final product, and the raw materials and equipment used in the synthesis process are simple, the production process is easily expanded to an industrial scale, and has good prospects for industrial production.

[0021] The layered mordenite synthesized in the present invention can be used as a carrier of a Ti-MOR catalyst. The introduction of the Ti element enhances the redox ability of the catalyst, thereby improving the reaction rate and selectivity, and is particularly suitable for catalytic applications such as organic pollutant degradation and waste gas treatment.

[0022] The present invention controls the temperature, time and molar ratio precisely, so that the synthesized mordenite not only has excellent crystal morphology, but also can effectively improve the stability and catalytic activity of the Ti-MOR catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The present invention will be further described below in conjunction with the accompanying drawings.

[0024] Figure 1 is the XRD spectrum of mordenite MOR-1;

[0025] Figure 2 is the SEM picture of mordenite MOR-1;

[0026] Figure 3 is the SEM picture of mordenite MOR-D1;

[0027] Figure 4 is the SEM picture of mordenite MOR-D3;

[0028] Figure 5 It is the XRD spectrum of the sample of comparative example 4;

[0029] Figure 6 This is the XRD spectrum of the sample in comparative example 5. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The layered mordenite provided by the present invention is prepared by mixing, stirring, crystallizing, drying and calcining raw materials, wherein the raw materials include a silicon source, an aluminum source, an alkali source, an additive and water;

[0032] The silicon source is C-type silica gel; the aluminum source is aluminum hydroxide; the alkali source is sodium hydroxide; and the auxiliary agent is pentamethylenediamine or hexamethylenediamine.

[0033] In some specific embodiments of the present invention, the aluminum source is calculated as aluminum oxide, the silicon source is calculated as silicon oxide, and the alkali source is calculated as sodium oxide. The molar ratio of aluminum oxide, silicon oxide, sodium oxide, additive and water in the raw materials is 1:(8-31.5):(2.25-4.75):(0.6-5):(300-450).

[0034] The invention realizes accurate control of raw materials in the process of synthesizing mordenite by adjusting the raw material composition and the proportion thereof, thereby improving the consistency and repeatability of the product.

[0035] The present invention also provides a method for preparing the layered mordenite, comprising the following steps:

[0036] S1. Mix deionized water, alkali source and aluminum source and stir for 10 minutes;

[0037] S2, adding an auxiliary agent and a silicon source to the mixture of S1 in sequence, stirring for 60 to 120 minutes to obtain a mixture to be crystallized;

[0038] S3, the mixture to be crystallized is placed in a crystallization kettle, the temperature is raised to 160°C to 170°C, and the temperature is kept for 22 to 34 hours;

[0039] S4. After the heat preservation is completed, the kettle is cooled down, the solid and liquid are separated, and the solid product is washed with deionized water until it is neutral, dried at 80°C to 120°C for 12 to 14 hours, and calcined at 500 to 600°C for 4 to 6 hours to obtain mordenite.

[0040] In some preferred embodiments of the present invention, the drying temperature is 100° C. to 120° C. In some other preferred embodiments of the present invention, the calcining temperature is 500° C. to 550° C.

[0041] The present invention provides an application of mordenite in the preparation of a Ti-MOR catalyst, wherein the mordenite is the mordenite described in the above technical solution.

[0042] Ti-MOR catalyst is a MOR-type catalyst with titanium (Ti) as an important component. When the Ti element is incorporated into the MOR structure, it can introduce acidic centers and redox active sites, which makes the Ti-MOR catalyst have special catalytic properties, especially in oxidation reactions and selective catalytic oxidation (such as organic pollutant degradation, air purification, etc.).

[0043] The mordenite of the invention can be used as a carrier for preparing Ti-MOR catalysts and has wide applications in organic pollutant degradation, air purification, petrochemical industry, waste gas treatment, automobile tail gas purification, etc.

[0044] In order to further illustrate the present invention, the following examples are used to describe the present invention in detail. The raw materials used in the following examples and comparative examples of the present invention are as follows:

[0045] Sodium hydroxide (purity greater than 99%) was purchased from Dalian Shengjia Chemical; aluminum hydroxide (purity 65%) was purchased from Tianjin Komiou Chemical Reagent Co., Ltd.; pentamethylenediamine (purity greater than 98%) was purchased from Shanghai Adamas Reagent Co., Ltd.; hexamethylenediamine (purity greater than 99%) was purchased from Shanghai Adamas Reagent Co., Ltd.; C-type silica gel (100 mesh, silica content 95%) was purchased from Shandong Xinhua Silica Gel Co., Ltd. White carbon black (silicon oxide mass content greater than 99.8%) was purchased from Jiangxi Black Cat Carbon Black Co., Ltd.

[0046] The XRD characterization of the catalysts in the following examples and comparative examples of the present invention was measured by an X-ray diffraction analyzer (PANalytical, X'Pert3 Powder); the scanning electron microscopy (SEM) characterization of the catalysts was measured by a scanning electron microscope (Hitachi, SU5000).

[0047] Example 1 A method for synthesizing layered mordenite, comprising the following steps:

[0048] 58.85g of deionized water, 2g of sodium hydroxide and 2.67g of aluminum hydroxide were mixed and stirred for 10min, and 0.77g of hexamethylenediamine and 5.62g of C-type silica gel were added in sequence and stirred for 60min. The mixture was charged into a 200ml crystallization kettle, heated to 160°C and kept warm for 22h. After the end of the warming, the kettle was cooled down and the solid-liquid separation was carried out. The solid product was washed with water until neutral, dried at 100°C for 14h, and calcined at 500°C for 6h to obtain mordenite, which was recorded as MOR-1.

[0049] The XRD spectrum and SEM photos of sample MOR-1 are attached. Figure 1 and attached Figure 2 .

[0050] Example 2 A method for synthesizing layered mordenite, comprising the following steps:

[0051] 78.45g of deionized water, 3.33g of sodium hydroxide and 2.67g of aluminum hydroxide were mixed and stirred for 10min, and 2.58g of hexamethylenediamine and 14.05g of C-type silica gel were added in sequence and stirred for 60min. The mixture was charged into a 200ml crystallization kettle, heated to 160°C and kept warm for 22h. After the end of the insulation, the mixture was cooled down and taken out of the kettle for solid-liquid separation. The solid product was washed with water until neutral, dried at 100°C for 14h, and calcined at 500°C for 6h to obtain mordenite, which was recorded as MOR-2.

[0052] Example 3 A method for synthesizing layered mordenite, comprising the following steps:

[0053] 88.73g of deionized water, 4.22g of sodium hydroxide and 2.67g of aluminum hydroxide were mixed and stirred for 10min, and 2.32g of hexamethylenediamine and 8.78g of C-type silica gel were added in sequence and stirred for 60min; the above mixture was charged into a 200ml crystallization kettle, heated to 160°C and kept warm for 22h, after the end of the insulation, the temperature was lowered and the kettle was taken out, the solid and liquid were separated, and the solid product was washed with water until neutral, dried at 100°C for 14h, and calcined at 500°C for 6h to obtain mordenite, which was recorded as MOR-3.

[0054] Example 4 A method for synthesizing layered mordenite, comprising the following steps:

[0055] 68.27g of deionized water, 3.78g of sodium hydroxide and 2.67g of aluminum hydroxide were mixed and stirred for 10min, and 0.91g of pentamethylenediamine (purity greater than 99%, the same below) and 17.57g of C-type silica gel were added in sequence and stirred for 60min; the above mixture was charged into a 200ml crystallization kettle, heated to 170°C and kept warm for 30h, after the end of the insulation, the kettle was cooled down, the solid-liquid separation was carried out, and the solid product was washed with water until neutral, dried at 120°C for 14h, and calcined at 550°C for 4h to obtain mordenite, which was recorded as MOR-4.

[0056] Example 5 A method for synthesizing layered mordenite, comprising the following steps:

[0057] 48.49g of deionized water, 4g of sodium hydroxide and 2.67g of aluminum hydroxide were mixed and stirred for 10min, and 2.04g of pentamethylenediamine and 12.65g of C-type silica gel were added in sequence and stirred for 60min. The mixture was charged into a 200ml crystallization kettle, heated to 170°C and kept warm for 30h. After the end of the insulation, the mixture was cooled down and taken out of the kettle for solid-liquid separation. The solid product was washed with water until neutral, dried at 120°C for 12h, and calcined at 550°C for 4h to obtain mordenite, which was recorded as MOR-5.

[0058] Comparative Example 1

[0059] 58.82g of deionized water, 2.44g of sodium hydroxide and 2.67g of aluminum hydroxide were mixed and stirred for 10min, and 6.32g of type C silica gel was added and stirred for 60min. The mixture was charged into a 200ml crystallization kettle, heated to 170℃ and kept warm for 30h. After the end of the insulation, the mixture was cooled down and taken out of the kettle for solid-liquid separation. The solid product was washed with water until neutral, dried at 120℃ for 12h, and calcined at 550℃ for 4h to obtain mordenite, which was recorded as MOR-D1.

[0060] See the attached SEM photo of sample MOR-D1 Figure 3 .

[0061] Comparative Example 2

[0062] 44.42g of deionized water, 3.56g of sodium hydroxide and 2.67g of aluminum hydroxide were mixed and stirred for 10min, 14.05g of type C silica gel was added and stirred for 60min; the mixture was charged into a 200ml crystallization kettle, heated to 170℃ and kept warm for 30h, after which the temperature was lowered and the kettle was taken out for solid-liquid separation, and the solid product was washed with water until neutral, dried at 120℃ for 12h, and calcined at 550℃ for 4h to obtain mordenite, recorded as MOR-D2.

[0063] Comparative Example 3

[0064] 79.16g of deionized water, 4.44g of sodium hydroxide and 2.67g of aluminum hydroxide were mixed and stirred for 10min, and 3.87g of hexamethylenediamine and 20.03g of white carbon black (with a silicon oxide mass content of greater than 99.8%) were added in sequence, and stirred for 60min; the above mixture was charged into a 200ml crystallization kettle, heated to 160°C and kept warm for 22h, and after the insulation was completed, the temperature was lowered and the kettle was taken out, the solid and liquid were separated, and the solid product was washed with water until neutral, dried at 100°C for 14h, and calcined at 500°C for 6h to obtain mordenite, which was recorded as MOR-D3.

[0065] See the attached SEM photo of sample MOR-D3 Figure 4 .

[0066] Comparative Example 4

[0067] 63.07g of deionized water, 2.98g of sodium hydroxide and 2.67g of aluminum hydroxide were mixed and stirred for 10min, and 7.75g of hexamethylenediamine and 21.43g of C-type silica gel were added in sequence and stirred for 60min; the above mixture was placed in a 200ml crystallization kettle, heated to 160℃ and kept warm for 22h, cooled down after the end of the warming, taken out of the kettle, and the solid-liquid separation was carried out, and the solid product was washed with water until neutral, dried at 100℃ for 14h, and calcined at 500℃ for 6h to obtain a sample, and its XRD photo is shown in the attached Figure 5 .

[0068] Depend on Figure 5 It can be seen that mordenite cannot be obtained when the dosage of the additive is too high.

[0069] Comparative Example 5

[0070] 58.22g of deionized water, 2.22g of sodium hydroxide and 2.67g of aluminum hydroxide were mixed and stirred for 10min, 8.51g of pentamethylenediamine and 18.27g of C-type silica gel were added in sequence and stirred for 60min; the above mixture was placed in a 200ml crystallization kettle, heated to 160℃ and kept warm for 22h, cooled down after the end of the warming, taken out of the kettle, and the solid-liquid was separated, and the solid product was washed with water until neutral, dried at 100℃ for 14h, and calcined at 500℃ for 6h to obtain a sample, and its XRD photo is shown in the attached Figure 6 .

[0071] Depend on Figure 6 It can be seen that mordenite cannot be obtained when the dosage of the additive is too high.

[0072] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A layered mordenite, characterized in that: The raw materials are mixed, stirred, crystallized, dried and calcined, and the raw materials include silicon source, aluminum source, alkali source, auxiliary agent and water; The silicon source is C-type silica gel, and the auxiliary agent is pentamethylenediamine or hexamethylenediamine.

2. The layered mordenite according to claim 1, characterized in that: The aluminum source is aluminum hydroxide, and the alkali source is sodium hydroxide.

3. The layered mordenite according to claim 2, characterized in that: The aluminum source is calculated as aluminum oxide, the silicon source is calculated as silicon oxide, and the alkali source is calculated as sodium oxide. The molar ratio of aluminum oxide, silicon oxide, sodium oxide, auxiliary agent and water in the raw materials is 1:(8-31.5):(2.25-4.75):(0.6-5):(300-450).

4. The method for preparing the layered mordenite according to any one of claims 2 to 3, characterized in that: The following steps are involved: After deionized water, alkali source and aluminum source are evenly mixed, auxiliary agent and silicon source are added in sequence, and the mixture to be crystallized is obtained after stirring. The mixture to be crystallized is then crystallized. After the crystallization is completed, the solid product is washed with water to neutrality, dried and calcined to obtain mordenite.

5. The preparation method according to claim 4, characterized in that: The crystallization temperature is 160° C. to 170° C., and the heat preservation time is 22 to 34 hours.

6. The preparation method according to claim 4, characterized in that: The drying temperature is 80° C. to 120° C., and the drying time is 12 to 14 hours.

7. The preparation method according to claim 6, characterized in that: The drying temperature is 100°C to 120°C.

8. The preparation method according to claim 4, characterized in that: The calcination temperature is 500° C. to 600° C., and the calcination time is 4 to 6 hours.

9. The preparation method according to claim 8, characterized in that: The calcination temperature is 500°C to 550°C.

10. Use of mordenite in the preparation of Ti-MOR catalyst, wherein the mordenite is the mordenite described in Examples 1 to 3 or the mordenite prepared by the method described in any one of Examples 4 to 9.